Pengaruh Shalat Berjamaah Terhadap Kedisiplinan Siswa Kelas III-VI Sekolah Dasar Negeri - Sholicha, Syovinatus; Ayunda, Ika; Indra Purnamanita, Eka Ismaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research was motivated by the researcher's curiosity about the influence of congregational prayer on student discipline. Apart from that, congregational prayer is a new program being implemented at SD Negeri Dadapan 04, Gucialit District, Lumajang Regency for the 2022/2023 academic year. Based on the background above, the discussion issues that can be taken up are: 1.) Is there an influence of congregational prayer on student discipline at SD Negeri Dadapan 04, Gucialit District, Lumajang Regency for the 2022/2023 academic year? 2.) How big is the influence of congregational prayers on student discipline at SD Negeri Dadapan 04, Gucialit District, Lumajang Regency for the 2022/2023 academic year? The aim of this research is: 1.) To determine the effect of congregational prayer on student discipline at SD Negeri Dadapan 04, Gucialit District, Lumajang Regency, academic year 2022/2023. 2.) To describe the influence of congregational prayers on student discipline at SD Negeri Dadapan 04, Gucialit District, Lumajang Regency, academic year 2022/2023. The method used in this research is a quantitative correlation research method and uses several data collection methods, namely, observation, interviews, questionnaires and documentation. From the data, the Chi Square Statistics results were significant. To ensure an increase in value, the coefficient formula is 17.12. The result contingency is 0.637 if consulted.